Lycopene supplementation reduces inflammatory, histopathological and DNA damage in an acute lung injury rabbit model - Fioretto, José Roberto [UNESP]; Klefens, Susiane Oliveira [UNESP]; Carpi, Mário Ferreira [UNESP]; Moraes, Marcos Aurélio [UNESP]; Bonatto, Rossano César [UNESP]; Ferreira, Ana Lúcia Anjos [UNESP]; Corrêa, Camila Renata [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Ronchi, Carlos Fernando (Associação de Medicina Intensiva Brasileira, 2025)
Objective: To investigate the effects of lycopene supplementation on inflammation, lung histopathology and systemic DNA damage in an experimentally induced lung injury model, ventilated by conventional mechanical ventilation and high-frequency oscillatory ventilation, compared with a control group. Methods: Fifty-five rabbits sampled by convenience were supplemented with 10mg/kg lycopene for 21 days prior to the experiment. Lung injury was induced by tracheal infusion of warm saline. The rabbits were randomly assigned to the control group and subjected to protective conventional mechanical ventilation (n = 5) without supplementation or the experimental group that was subjected to acute lung injury and provided conventional mechanical ventilation and high-frequency oscillatory ventilation with and without lycopene supplementation (n = 10 rabbits in each group). Lung oxidative stress and the inflammatory response were assessed based on the number of polymorphonuclear leukocytes in bronchoalveolar lavage fluid, DNA damage and pulmonary histological damage. Results: A significant worsening of oxygenation and a decrease in static lung compliance was noted in all groups after pulmonary injury induction (partial pressure of oxygen before 451.86 ± 68.54 and after 71 ± 19.27, p < 0.05). After 4 hours, the high-frequency oscillatory ventilation groups with and without lycopene supplementation as well as the group receiving protective conventional mechanical ventilation with lycopene supplementation showed significant oxygenation improvement compared with the protective conventional mechanical ventilation group without supplementation (partial pressure of oxygen of the group with mechanical ventilation without lycopene of 102 ± 42, of the group that received conventional protective mechanical ventilation with lycopene supplementation of 362 ± 38, of the high-frequency group without lycopene supplementation of 420 ± 28 and of the high-frequency group with lycopene supplementation of 422 ± 25; p < 0.05). Compared with rabbits not receiving supplementation, those in the groups that received protective conventional mechanical ventilation with lycopene supplementation and high-frequency oscillatory ventilation with lycopene supplementation had significantly less inflammation as well as less histological injury (p < 0.05). Compared with rabbits subjected to protective conventional mechanical ventilation, significantly lower DNA damage was observed in rabbits supplemented with lycopene (p < 0.05). Conclusion: Lycopene supplementation reduces inflammatory and histopathological lung injuries, regardless of the associated ventilatory mode. In addition, lycopene improved oxygenation and reduced DNA damage when protective conventional mechanical ventilation was used.
Keywords: Carotenoids; DNA damage; Inflammation; Lung injury; Respiration, artificial; Respiratory distress syndrome